Teresa Billington-Greig, 1909 (1909)
1909 1880-1914 "Teresa Billington-Greig, 1909" [EP0064], 1909 This article on 'Leaders and speakers in the women's suffrage movement' is from The Queen, the Lady's Newspaper for 27 February, 1909. It features a photograph and article on Teresa Billington-Greig, the founder of the Equal Pay League in 1904. The League later became the National Union of Women Teachers, which continued to campaign for equal pay in teaching until 1961.